Rethinking metonymy : literary theory and poetic practice from Pindar to Jakobson - Matzner, Sebastian (Classics in theory, 2016)
'Rethinking Metonymy' confronts and resolves issues surrounding problematic appropriations of metonymy in the humanities. By developing a ground-breaking new definition based on analysis of examples in Greek tragedy and lyric poetry, it sets an agenda for far-reaching reconsiderations in literary studies and beyond